Comparative study using routine stains and Immunohistochemistry staining techniques for detection of Helicobacter pylori - Dr. Priyadarshini MM; Dr Manjunatha Y.A; Dr Shaista Choudhary; Dr Suba G (Tropical Journal of Pathology and Microbiology, 2018)
Introduction: The aim of this study was to evaluate the role of endoscopic biopsies for detection of Helicobacter Pylori using routine staining techniques which included hematoxyline and eosin, Giemsa and Immunohistochemistry.Methods: A prospective study of 3 years in which 53 gastric endoscopic mucosal biopsies were included. These patients had a clinical history of dyspeptic symptoms. 3 staining techniques were used to identify H. Pylori. Hematoxylin and eosin staining was done routinely along with Giemsa and H. Pylori detection using antibodies directed against specific antigens in IHC. The staining pattern of H. Pylori was also studied.Results: In 53 cases studied, modified Giemsa staining is the cheapest and easiest to perform but antibodies directed against specific antigens in IHC proved to be more specific in identifying H. Pylori than other staining techniques. While Giemsa staining was non-specific for other species of Helicobacter IHC was specific for H. Pylori. Spiral type of staining was the most frequent of the staining pattern.Conclusion: Our study highlighted the association of Helicobacter Pylori in patients with functional dyspepsia and proved Immunohistochemistry as gold standard in identifying Helicobacter Pylori with Geimsa being practically applicable in Indian set up keeping the cost factor in mind.